2020
DOI: 10.1177/0095244320939995
|View full text |Cite
|
Sign up to set email alerts
|

Layer-to-layer physical characteristics and compression behavior of 3D printed polymer metastructures fabricated using different process parameters

Abstract: The extrusion-based three-dimensional printing technology such as fused deposition modeling (FDM) is the widely used one owing to its low cost. The FDM method can be used to fabricate parts with different fill densities, fill patterns, and process parameters such as extrusion temperature and print speed. In this research, influence of process parameters such as extrusion temperature and print speed on the physical characteristics such as the shape and the size of printed fibers in each layer, the fiber distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…This effect has been observed in some work with ABS (Patibandla and Mian, 2020) and PLA (Kuznetsov et al , 2020). One study in ABS reported that increasing PS from 100 to 150 mm/s slightly increased the tensile modulus but had no effect on strength properties (Patibandla and Mian, 2020). In PLA, increasing PS had a minor but positive effect on tensile strength (Kuznetsov et al , 2020).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This effect has been observed in some work with ABS (Patibandla and Mian, 2020) and PLA (Kuznetsov et al , 2020). One study in ABS reported that increasing PS from 100 to 150 mm/s slightly increased the tensile modulus but had no effect on strength properties (Patibandla and Mian, 2020). In PLA, increasing PS had a minor but positive effect on tensile strength (Kuznetsov et al , 2020).…”
Section: Discussionsupporting
confidence: 64%
“…This has been expected to hold the temperature above the glass transition temperature longer, allowing for entanglement of polymer chains and increasing stiffness and strength (Lee and Wu, 2020). This effect has been observed in some work with ABS (Patibandla and Mian, 2020) and PLA (Kuznetsov et al, 2020). One study in ABS reported that increasing PS from 100 to 150 mm/s slightly increased the tensile modulus but had no effect on strength properties (Patibandla and Mian, 2020).…”
Section: Print Speedmentioning
confidence: 87%
See 1 more Smart Citation
“…The stress in compression largely exceeded that measured in the tension, for any given strain. A strong tension and compression asymmetry was observed [ 32 , 33 ]. This was caused by the residual stress, which was due to the cooling down of the specimen to room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The direct mechanical wear between triboelectric materials leads to TENG devices' poor stability with unstable outputs. Studies have shown that increasing the porosity of materials and decreasing the effective Young's modulus make the triboelectric materials more deformable and increase the effective contact area, resulting in an improved TENG performance and mechanical stability, 94,119,145,146,157 through introducing 3D printed metastructure, [158][159][160] auxetic structures, [161][162][163] and so forth. For instance, Matlack et al 158 suggested that the 3D-printed meta-structure with embedded resonators could not only reduce the overall mass of the device but also expand and reduce the Bragg gap, which has a unique advantage for the absorption of low-frequency vibration energy.…”
Section: Engineering Mechanical Properties Of the Triboelectric Layersmentioning
confidence: 99%